IDENTIFICATION OF STRATEGIES FOR URBAN AGRICULTURE DEVELOPMENT: A SWOT ANALYSIS - Ramaloo, Pushpawani; Siwar, Chamhuri; Yeun Liong, Choon; Isahak, Anizan (PLANNING MALAYSIA, 2018)
Population growth is the major reason for increased food demands and countries face difficult challenges in ensuring food security. This study was conducted to investigate the prospects of urban agriculture (UA) development in Penang state, Malaysia, from the experts’ perspective, particularly on the strengths, weaknesses, opportunities and threats (SWOT). Fifty-seven Penang state stakeholders were interviewed. This study applied qualitative analysis method using SWOT analysis to identify and prioritize strategies for urban agricultural development in order to assist planners to manage urban agriculture for achieving food security in urban areas. Based on the results of the SWOT analysis, strategic plans for urban agriculture development system were prioritized into legal framework, financial, infrastructure, land, water, environment and health, social, marketing, and research and development aspects. Finally, a number of strategies for sustainable development of urban agriculture were outlined in order to reduce the weaknesses, avoid the threats, improve the strengths, and grasp the opportunities for the development of urban agriculture production in the Penang state.